Private Saving in Ghana: The Combined Efforts of Financial Development, Interest Rates, and Inflation - Alnaa, Samuel Erasmus; Matey, Juabin (Asian Development Policy Review, 2022)
Understanding private saving behavior of the citizenry is crucial for informed policy decisions in an economy. The reason is not far-fetched; economies gain sustained growth from investment through a positive saving culture. However, much of the available literature is on aggregate savings rather than on private saving behavior. This study looks at the combined effects of financial development, interest rates and inflation rates on private saving behavior among Ghanaians. Data for the study were obtained from the World Bank Development Indicators between 1980 and 2019. Johansen’s cointegration test was employed, and attempts were made to ascertain the existence of a long-run relationship among variables using the vector autoregressive (VAR) model. The study confirms a significant positive relationship between private saving behavior and financial sector development. This partly explains the relevance of deepening the financial sector through reductions in costs of performing transactions and initiating contracts to encourage private saving through improved propensity to save by the old and to attract new entrants. A reliance on macroeconomic variables to forecast the behavior of private saving enjoins policy decision makers to consider the implications of their decisions for private saving. Among the recommendations are, lower borrowing costs across the economy, resulting in increased investment and consumption spending, and hence economic recovery in times of stagnation.